Anteseden Kepuasan Kerja Karyawan PT. BPR Buana Artha Lestari Surakarta - darmawan, intan (JURNAL EKOMAKS : Jurnal Manajemen, Ekonomi Kreatif dan Bisnis, 2020)
Abstract— The purpose of this study is to examine the effect of work environment, leadership style, and organizational culture on employee job satisfaction. Data were collected from 50 employee’s working at PT BPR Buana Artha Lestari Surakarta. The statistical method is multiple linear regression with the SPSS version 20 software. The results of this study indicate that the work environment, leadership style, and organizational culture have a positive and significant effect on employee job satisfaction.Keywords—: Work environment, Leadership style, Organizational culture; Job satisfaction.